Efforts to Motivate Youth Indonesian Christian Church of the Royal Family, Salatiga, Central Java in Spiritual Maturity - Kartika Dewi Kristanti; Yusak Tanasyah; Margreth Luciyanna Risakotta; Mieki Cynthia Kurniawan (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2024)
This study examines the various efforts undertaken by the Indonesian Christian Church of the Royal Family in Salatiga, Central Java, to foster spiritual maturity among its youth members. Recognizing the pivotal role of youth in the church's future, the church employs a multifaceted approach to ensure their spiritual growth and active participation in religious life. Key strategies include structured Bible study programs, youth fellowship activities, leadership training, and community service projects. The church also emphasizes the importance of mentorship, with older, spiritually mature members guiding the younger generation. These efforts are designed to address the unique spiritual needs of young people, providing them with a supportive environment where they can explore their faith, develop a personal relationship with God, and grow in their understanding of Christian principles. The effectiveness of these initiatives is evaluated through qualitative methods, including interviews and participant observation, revealing significant positive impacts on the spiritual lives of the youth. This research contributes to the broader discourse on youth ministry by highlighting successful practices that can be replicated in similar contexts to nurture spiritual maturity among young Christians.